(untitled) (Bioscience Journal, 2018)
This study evaluated the adjustment of four kinetic models and their respective parameters on data of dairy wastewater treatment by the physico-chemical process of flotation and ozonation. The experiment was implemented during the year 2014, with all the tests in triplicate. The treatments were carried out at different pH levels (3.6, 7.0 and 10.4), and flotation/ozonation was catalyzed by manganese (Mn2+) in neutral level (pH 7.0). Best removal efficiencies for chemical oxygen demand (COD) were obtained in acidic medium, with removals greater than 75% after 20 min of treatment. There was no significant difference with regards to addition of Mn2+ on COD removal by the physico-chemical process. The kinetic models that best fit to the experimental data, for all treatments, were the asymptotic (residual) model and that of Chan and Chu. Treatment in acidic medium showed the highest values of the kinetic parameters for the adjusted model, obtaining a k coefficient equal to 0.2394 min-1 for the asymptotic model and kinetic coefficient 1/Ï of 0.4816 min-1 for the Chan and Chu model, both presenting a determination coefficient greater than 99%.